Faktor Risiko Kelelahan Kerja Pada Pekerja Stasiun Pengisian Bahan Bakar Umum (SPBU) Di Kebun Cengkeh Tahun 2020 - Zulfikar Lating; Sahrir Sillehu; Sartika Maya Sary Sumanjaya (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Work fatigue has a risk where workers who work in a tired state have a tendency to decrease physical and psychological abilities which can have an impact on being careless and not careful in doing work so that it can cause work accidents to themselves and others. The purpose of the study was to determine the relationship between age, length of work, workload and work fatigue. This research is a quantitative research, analytic survey research type using a cross sectional approach with 33 respondents. Sampling technique Total sampling. Statistical analysis of Chi Square test using an instrument questionnaire. The results of the study found that the relationship between age and delaying work fatigue in refueling station workers at Ambon Clove Gardens in 2020, with Chi-Square statistical values, obtained p value = 0.004 (p < = 0.05) and the relationship between length of work and complaints Work Fatigue in Refueling Station Workers at Ambon Clove Gardens in 2020, with a Chi-Square statistical value, obtained p value = 0.027 (p<α = 0.05) and Work Relationship with Complaints of Work Fatigue at Refueling Station Workers in Ambon Clove Garden 2020. Based on the value of the Chi-Square statistical test, p value = 0.034 (p <α = 0.05). Keywords: Age, length of working, workload, work fatigue